PTU-081 CD151 In Chronic Liver Disease and HCC - A New Player in T Cell Recruitment to The Liver. (17th August 2016) - Wadkin, JCR; Patten, DA; Kamarajah, SK; Weston, C; Shetty, S
Abstract : Introduction: Inflammation of the liver drives the onset and progression of chronic liver diseases whilst fostering an environment where the formation of neoplastic tumours such as hepatocellular carcinomas (HCC) can occur. A key step in this process is leukocyte recruitment via hepatic sinusoidal endothelial cells. CD151, a member of the tetraspanin family, has been shown to regulate heterotypic partner proteins involved in leukocyte recruitment and therefore an understanding of the expression and function of CD151 in the liver could identify new organ-specific anti-inflammatory therapies. Methods: We used immunohistochemistry, dual colour immunofluorescence co-localisation studies, qRT-PCR and western blotting to determine the cell specific expression of CD151 in pathological control liver, chronic liver diseases and tissue taken from patients with HCC. Cell-based ELISA, qRT-PCR and western blotting were then used to determine the regulation of CD151 expression by hepatic sinusoidal endothelial cells (HSEC) following growth factor and cytokine treatment to mimic inflammatory and tumourigenic environments. Flow-based adhesion assays were used to study the role of CD151 in the adhesion of Jurkat cells, a human T cell line, to HSEC monolayers with subsequent immunofluorescence analysis. Results: Increased CD151 protein expression was associated with areas of fibrosis and neovascularisation, particularly in parenchymal liver disease such as alcoholic and non-alcoholic fatty liver disease as well as in HCC. CD151 was highly expressed by HSEC both within liver tissue and in vitro . The expression of CD151 in HSEC was upregulated by stimulation with tumour cell line supernatant or a combination of hepatocyte and vascular endothelial growth factors. We found CD151 molecules clustering around adherent Jurkat cells following capture from flow by HSEC monolayers. Function-blocking antibodies to CD151 significantly reduced adherence of Jurkat under conditions of shear stress. Conclusion: We demonstrate for the first time the expression of CD151 on human sinusoidal endothelial cells and that this molecule is expressed in neovessels in chronic liver disease and HCC. We also demonstrate that CD151 is upregulated by pro-tumourigenic factors on HSEC and functionally plays a role in T cell adhesion to HSEC. These findings further our understanding of liver inflammation and lymphocyte recruitment to the organ, in both chronic and malignant disease, and could form the basis of a potential therapeutic target. Disclosure of Interest: None Declared